Organic extracts of Asian plants potentially support thrombolysis in varied BMI groups - Kabir, Md. Imtiazul; Rahman, Md. Mominur; Rahman, Md. Atiar; Kamal, A.T.M. Mostafa; Md. Adnan; Auniq, Reedwan Zafar; Uddin Chy, Md. Nazim; Hasan, Md. Mehedi; Haque, Md. Areeful; Bhuiyan, M. Mosharef Hossain; Dina Hajjar; Makki, Arwa A.; et al. (Penerbit Universiti Kebangsaan Malaysia, 2020)
A number of plant-derived drugs have been prescribed for treating atherothrombotic disorders such as myocardial or cerebral infarction. Therefore, this study investigated the individual and combined antithrombotic effects of six Asian plants on individuals with various BMIs. Venous blood drawn from healthy volunteers was allowed to form clots and treated with six organic fractions of Ophiorrhiza harrisiana Heyne, Haldina cordifolia (Roxb.) Ridsdale, Eclipta alba (L.) Hassk, Syzygium operculatum L., Lantana camara L., and Acanthus ilicifolius Linn. using the clot-lysis method. The weight of the clot before and after treatment provided the percentage of clot lysis. Variations in clot lysis in different BMI groups were assessed. A. ilicifolius induced the most thrombolytic activity, whereas L. camara showed slightly lower thrombolytic activity. The maximum clot-lysis activity was primarily observed in different fractions of O. harrisana, H. cordifolia, E. alba, S. operculatum, and A. ilicifolius. However, chloroform fractions of all plants except O. harrisana and L. camara showed maximum activity in individual plants. O. harrisana, H. cordifolia, E. alba, S. operculatum, L. camara, and A. ilicifolius showed the highest significant (P < 0.5 and P < 0.001) clotlysis activity viz., 46.60±0.79% (ethyl acetate), 55.40±1.023% (chloroform), 48.86±1.35% (CCl4 ), 44.89±1.76% (chloroform), 29.17±1.12% (ethanol), and 56.318±1.64% (chloroform). Obtained results were verified by ligandreceptor interaction through in silico approach. In conclusion, H. cordifolia, E. alba, and A. ilicifolius demonstrated promising thrombolytic effects; therefore, it is recommended that they be studied further for their therapeutic potential.